(x+3)⁴ - 13(x+3)² + 36 = 0
Замена:
(х+3)² = у
(х+3)⁴ = у²
ОДЗ: у ≥ 0
данное уравнение примет вид:
у² - 13у + 36 = 0
D = 13² - 4·1·36 = 169 - 144 = 25 = 5²
y₁ = (13-5)/2 = 8/2 = 4
y₂ = (13+5)/2 = 18/2 = 9
Находим х с уравнения (х+3)² = у
1) При у₁ = 4
(х+3)² = 4
х + 3 = √4
х + 3 = 2 => x₁ = - 1
х + 3 = - 2 => x₁ = - 5
2) При у₂ = 9
(х+3)² = 9
х + 3 = √9
х + 3 = 3 => x₃ = 0
х + 3 = - 3 => x₄ = - 6
ответ: {- 6; - 5; - 1; 0}
45*Х+1=50*(Х-1)-4
45Х+1=50Х-50-4
54+1=50Х-45Х
55=5Х
Х=11
45*11+1=496
50*(11-1)-4=50*10-4=500-4=496
496=496
ответ 496 тетрадей.